PERANAN GUIDE LOKAL DAN MASYARAKAT UNTUK MENINGKATKAN EKSISTENSI DESA WISATA SASAK ENDE - Lalu Ahmad Madani,; Surayyal Hizmi,; Endang Sri Wahyuni, (Juremi: Jurnal Riset Ekonomi, 2024)
This research discusses the role of the community and local guides in improving the existence of Sasak Ende Tourism Village in Lombok. Although the village has an interesting cultural uniqueness, it is less well known than other destinations on the island, due to the lack of community participation in developing and promoting this village. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that local communities and guides have an important role in preserving local customs and culture, welcoming tourists with hospitality, and providing quality information and services to promote the village through various platforms, including social media. In conclusion, the active involvement of the community and local guides contributed significantly to the increasing popularity and attractiveness of Sasak Ende Tourism Village, with suggestions for future research exploring